Determinan Harapan Peserta Jaminan Kesehatan Nasional Terhadap Layanan Di Klinik Pratama Kota Depok Periode Mei Tahun 2016 - Aini, Baiq Qurrata; Damayanti, Rita (UI Scholars Hub, 2017)
The score of JKN member’s satisfaction in primary clinic in 2014 reached as high as 80%, which means that it achieved the target of Jaminan Kesehatan Nasional’s (JKN) Road Map. However, there were still many complaints coming from the BPJS customer as shown in YLKI report and in Kemenpan official website regarding unfulfillment of their expectations. This study aimed to obtain information about the determinant of member’s expectation to the service of primary clinic in Depok (May 2016). This study combined qualitative and quantitative study by sequential exploratory, which was started by qualitative study to explore the phenomena and then followed by quantitative design. The number of participants in the qualitative and quantitative study were 12 and 203, respectively. The result showed that there were no correlation between gender, age, and occupation with the level of their expectation. On the other hand, there were correlation observed between the level of education, personal need, word-of-mouth, and past experience with the level of their expectation. The most dominant factor that influences the level of respondent’s expectation was personal need, which means that the higher respondent frequency to visit primary clinic to get treatment when sick, the higher the level of respondent expectation